2011
DOI: 10.1080/07481187.2010.511424
|View full text |Cite
|
Sign up to set email alerts
|

Ghosts, Meaning, and Faith: After-Death Communications in Bereavement Narratives

Abstract: After-death communications (ADCs) are reported encounters with a deceased loved one, a contemporary type of ghost experience heralded as therapeutic in coping with bereavement. Pertinent literature generally illustrates the healing power of ADCs with brief self-contained episodes. The functions of ADCs over the course of grief need exploration. To that end, this article analyzes 20 published book-length autobiographical stories of bereavement in which authors report ADCs. Two functional patterns are identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
6
17
0
Order By: Relevance
“…During normal bereavement, the need to maintain attachment relationships increase and, for some, attachment-seeking efforts include communicating with ghosts or apparitions of the deceased (Kwilecki, 2011) or sensing the presence of the deceased during daily activities (Steffen & Coyle, 2011). Study findings have suggested that these supernatural experiences may compensate for anxious attachment experiences from early childhood.…”
Section: Unresolved Mourning Supernatural Belief Fantasy and Dissomentioning
confidence: 96%
“…During normal bereavement, the need to maintain attachment relationships increase and, for some, attachment-seeking efforts include communicating with ghosts or apparitions of the deceased (Kwilecki, 2011) or sensing the presence of the deceased during daily activities (Steffen & Coyle, 2011). Study findings have suggested that these supernatural experiences may compensate for anxious attachment experiences from early childhood.…”
Section: Unresolved Mourning Supernatural Belief Fantasy and Dissomentioning
confidence: 96%
“…While such discussions would usually be outside the social norm, these parents did not feel that it was unusual for them to be experiencing such phenomena, often in the form of after-death communications. Such experiences were reported to offer pain relief to bereaved people (Kwilecki, 2011). Discussions about ritual and supernatural phenomena voiced the parents' sense of the continuation of the emotional connection developed with their child during their life that had continued.…”
Section: Still Part Of the Family 63mentioning
confidence: 98%
“…R. Jahn and S. Spencer-Thomas relationship continues with an evolving mental and emotional connection (Kwilecki, 2011). This continuing bond can happen on two levels (Gee, 2009).…”
mentioning
confidence: 98%